1994
DOI: 10.1007/bf00414183
|View full text |Cite
|
Sign up to set email alerts
|

The neurite growth promoting protease nexin 1 in glial cells of the olfactory bulb of the gerbil: An ultrastructural study

Abstract: The glia-derived serine protease inhibitor and neurite outgrowth promoter protease nexin-1 (PN-1) is expressed in Schwann cell precursors and astroblasts during embryogenesis. In the adult nervous system, PN-1 persists in the Schwann cells and olfactory glia only. Light-microscopic immunohistochemistry has revealed the presence of PN-1 in the olfactory mucosa and in the nerve fiber layer of the olfactory bulb. The present electron-microscopic study of the gerbil olfactory bulb confirms the occurrence of PN-1 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Interestingly, the ONL of the olfactory bulb is the only site in the mammalian CNS where ACs also express glia-derived nexin (Scotti et al, 1994). Whether this reflects some special property of olfactory bulb ACs as a result of their close spatial association with OECs, or whether OEC function is influenced by surrounding ACs remains to be elucidated.…”
Section: Relationship Between Olfactory Ensheathing Cells and Developmentioning
confidence: 96%
“…Interestingly, the ONL of the olfactory bulb is the only site in the mammalian CNS where ACs also express glia-derived nexin (Scotti et al, 1994). Whether this reflects some special property of olfactory bulb ACs as a result of their close spatial association with OECs, or whether OEC function is influenced by surrounding ACs remains to be elucidated.…”
Section: Relationship Between Olfactory Ensheathing Cells and Developmentioning
confidence: 96%
“…In addition to GDNF, Nogo and Slit-2, OECs produce numerous putative neuritogenic factors such as PN-1, AAP, L1 and bone morphogenetic protein 7 [52,53,54,55]. It is possible that like GDNF, many guidance factors produced by OECs may regulate both axonal extension and OEC migration.…”
Section: Regulation Of Oec Migration At a Molecular Levelmentioning
confidence: 99%
“…Within the nerve fiber layer (NFL) of the olfactory bulb, the plasma membranes of ensheathing cells and astrocytes frequently come into close contact with no intervening basal lamina (Doucette 1984(Doucette , 1990(Doucette , 1993aValverde and Lopez-Mascaraque 1991). At the electron microscopic level, Scotti et al (1994) noted the presence of gap junctions between astrocytes and ensheathing cells in the olfactory bulb of adult gerbils. Cx43 is most likely the connexin protein used to form these gap junctions, which allow ensheathing cells and astrocytes to communicate with one another along the CNS portion of the primary olfactory pathway.…”
Section: Expression Of a Non-myelinating Phenotype In Vivomentioning
confidence: 98%
“…Doucette (1990) suggested it was ensheathing cells that were responsible for its synthesis, and that it was an ideal molecular candidate for a chemotropic factor in the primary olfactory pathway. Subsequently, Scotti et al (1994) confirmed that the PN -1 protein was expressed by glial cells of the nerve fiber layer of the bulb, but they found its expression was not restricted to ensheathing cells. The astrocytes in this layer of the bulb, as well as in the adjacent part of the glomerular layer, also expressed the protein.…”
Section: Differentiation Into Mature Non-myelinating Cells: Postnatalmentioning
confidence: 99%
See 1 more Smart Citation